On the taxonomic status of Teyuwasu barberenai Kischlat, 1999 (Archosauria: Dinosauriformes), a challenging taxon from the Upper Triassic of southern Brazil - Garcia, Maurício S.; Müller, Rodrigo T.; Dias-Da-Silva, Sérgio (Zootaxa, 2019)
The controversial dinosauriform Teyuwasu barberenai Kischlat, 1999 (Fig. 1B) is based on a right femur (BSPG AS XXV 53) and tibia (BSPG AS XXV 54), formerly referred to the pseudosuchian ‘Hoplitosuchus raui’ (= Hoplitosaurus raui) Huene, 1938 (see also Huene, 1942). This material comes from a classic Late Triassic (Carnian) locality in southern Brazil (Fig. 1A), the Cerro da Alemoa outcrop on the Alemoa complex, that has yielded several noteworthy tetrapod specimens (see Garcia et al., 2019, for a complete list of references). When reviewing these abovementioned materials, Kischlat (1999) considered it to belong to a “robust saurischian dinosaur”, but later this taxon was considered to be a nomen dubium (Langer et al., 2010; Ezcurra, 2012). Foremost, the initial description of this taxon is problematic, because Kischlat (1999) presented it in a symposium abstract which does not constitute a published work [which is not allowed under the Art. 9.10 of the International Commission on Zoological Nomenclature (ICZN)]. Moreover, the author did not list traits that clearly differentiated Teyuwasu from other coeval dinosauriforms (cf. Art. 13 of the ICZN, see further below). In particular, it was not adequately distinguished from Staurikosaurus pricei Colbert, 1970 (Fig. 1B), which also comes from the same Alemoa complex, but from another nearby outcrop (Sanga Grande/Sanga de Baixo) considered equivalent in stratigraphic level and horizon with the lower levels of the Cerro da Alemoa site (Huene, 1942; Colbert, 1970; see also Garcia et al., 2019) (Fig. 1A). However, Huene (1942) did not clearly specify that the materials (femur and tibia) later assembled by Kischlat (1999) into the holotype of Teyuwasu were found in close association, although Huene (1942) cited that they come from the same stratigraphical level and horizon, and to our interpretation, their morphology and preservational features are compatible. Still, assigning these bones as part of a single individual is tentative.